Selection of Krathue (Zingiber zerumbet (L.)) Varieties in the Southern Region for the Production of Unique Flowering Plants and their Use as Herbal Tea - Pichaiyut, Nattayawan; Phongnarisorn, Benjapor; Suksamran, Chaiyapoom; Choopeng, Sopa (YRU Journal of Science and Technology, 2025)
Zingiber zerumbet, commonly known as Krathue, is a native plant of Southern Thailand, traditionally utilized as a spice, medicinal herb, and ornamental cut flower. However, most research has focused on breeding, production, and pharmacological studies. Therefore, the objectives of this research were to study Krathue varieties in Southern Thailand with potential to be a commercial local identity plant and add economic value by processing it into herbal tea products. It was found that Krathue Pilas and Kratheu Phee have potential as cut flowers, while Krathue Phrao is a species with potential for processing to create added value. The chemical analysis of the bracts and rhizomes of Krathue Phrao showed a pH of 5.78 and 6.33, soluble solids content of 0.009 and 0.057 °Brix, total phenolic compound content of 5.48 and 4.44 mg gallic acid equivalents per gram of dry weight, and high antioxidant activity by DPPH method of 68.34 and 61.85%, respectively. In addition, the bracts contained 1.83 percent fiber content on fresh weight. When developed into herbal tea products using a combination of bract powder, rhizome powder, and oolong tea powder in different ratios, the resulting products showed statistically significant differences in both physical and chemical aspects (p ≤ 0.05). The third experimental set, using mixed powders of bracts, rhizomes, and oolong tea at a ratio of 1:0.25:0.75, was the most suitable, with the highest overall preference score of 7.17 points. It also had the highest total phenolic compound content and antioxidant activity.